HUBUNGAN KECANDUAN GAMEONLINEDENGAN PRESTASI BELAJAR SISWA SMP NEGERI 1 KUTA - Pande, Ni Putu Arika Mulyasanti; Marheni, Adijanti (Jurnal Psikologi Udayana; Vol 2 No 2 (2015)DO - 10.24843/JPU.2015.v02.i02.p05, 2015)
Learning achievement can be defined as the result gained by students in mastering assignment or subject matter that is received in certain period. There are intenal and external factors that relates to learning achievement, one of them is onlinegame addiction. Students who addicted to onlinegame would reduce the time dedicated  to study and do homework, thus their learning achievement will likely be declined. Onlinegame addiction is a common phenomenon in adolescents. Thus, the researcher wants to find out the relationship between onlinegame addiction and learning achievement in students of SMP Negeri 1 Kuta. Subject in this research are 55 students in SMP Negeri 1 Kuta who meet the criteria for being 13-15 years old and playing onlinegame in more than 2 hours. Sampling method used purposive sampling. Research method used correlational study. Data are collected with questionnaire to measure onlinegame addiction and school grade to measure learning achievement. Result of assumption test shows data are normal and linear. Normality test of onlinegame addiction questionnaire shows significance level 0,534 and learning achievement shows significance level 0,819. Linearity test between onlinegame addiction and learning achievement has significance level 0,001. Result of this research finds negative significant relationship between onlinegame addiction and learning achievement and its correlational coefficient is -0,472.   Keyword:gameonline addiction, learning achievement, middle school student